Dekonstruksi Konsep dalam Kumpulan Puisi Selamat Menunaikan Ibadah Puisi Karya Joko Pinurbo - Darliani Darliani; Herson Kadir; Ellyana Hinta (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The purpose of this study is to describe the deconstruction of the meaning of the concept in the collection of poems Happy Performing Poetry Worship by Joko Pinurbo. The research method used is descriptive qualitative. Research data collection techniques used library study techniques, while data analysis techniques were more dominantly carried out to look at the interweaving of results of interpretation and description qualitatively. The results of the study show that there are 12 concepts of meaning that experience deconstruction which gives birth to an independent meaning that disassembles the stability of the concept of meaning in a contradictory manner. Twelve deconstructions of the concept of meaning in the poetry collection is identified as deconstruction through paradox, irony, and contradiction of the concept of meaning.